Comparative evaluation of triglyceride/high density lipoprotein cholesterol and C-reactive protein between ischemic stroke and healthy control group - Ouseph, Leena C.; Bhat, Sajad A.; John, Mathew (International Journal of Research in Medical Sciences, 2024)
Background: Triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-C) are predictive of the start of cardiovascular disease and metabolic syndrome. Dyslipidemia is a multifactorial disorder that exacerbates the vascular pathology associated with stroke. C-reactive protein (CRP) levels are elevated in people with a higher prevalence of stroke risk factors, such as hypertension, diabetes, and dyslipidemia. This study aims to compare and analyze the values of lipid ratio such as TG/HDL-C and inflammatory marker, CRP in acute ischemic stroke (AIS). Methods: This study was conducted at Jubilee Mission Medical College and Research Institute in Thrissur, Kerala. The duration of the research period was 2022 September to 2024 July. It was a prospective comparative cross sectional study. Data collection included physical, medical examinations and laboratory investigations. Statistical analysis was performed using statistical package for the social sciences (SPSS) version 26. Results: The comparison of inflammatory marker, CRP and lipid profile ratio such as TG/HDL-C showed an increased level in AIS than control. No correlation was observed between CRP and TG/HDL-C in AIS group. Conclusions: Our study observed that inflammatory markers especially CRP have strong predictive potential in diagnosing AIS. The lipid profile ratio such as TG/HDL-C have moderate predictive potential in AIS.